2018
DOI: 10.1021/acs.jafc.8b00330
|View full text |Cite
|
Sign up to set email alerts
|

Leucine Promotes the Growth of Fetal Pigs by Increasing Protein Synthesis through the mTOR Signaling Pathway in Longissimus Dorsi Muscle at Late Gestation

Abstract: Leucine (Leu) plays an important role in protein synthesis and metabolism. The present study tested whether Leu supplementation in the diet for sows during late pregnancy could improve piglet birth weight, and it also investigated the possible underlying mechanism. Two hundred sows at day 70 of pregnancy were selected and assigned to four groups fed with following four diets until farrowing, respectively: corn and soybean meal-based diet group (CON), CON + 0.40% Leu, CON + 0.80% Leu, and CON + 1.20% Leu. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Most studies reporting on fetal growth after BCAA supplementation were performed in rats ( n = 7) [ 43 , 97 , 98 , 99 , 100 , 101 , 102 ], with a few in mice ( n = 1) [ 103 ] and pigs ( n = 2) [ 104 , 105 ]; no human studies were found ( Table A5 ). Leucine was the most investigated BCAA ( n = 9) [ 43 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 105 ], followed by valine ( n = 4) [ 43 , 97 , 98 , 104 ], and isoleucine ( n = 3) [ 43 , 98 , 99 ]. The studies performed by Brunner [ 43 ], Matsueda [ 97 ], and Mori [ 98 ] used all three BCAAs.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies reporting on fetal growth after BCAA supplementation were performed in rats ( n = 7) [ 43 , 97 , 98 , 99 , 100 , 101 , 102 ], with a few in mice ( n = 1) [ 103 ] and pigs ( n = 2) [ 104 , 105 ]; no human studies were found ( Table A5 ). Leucine was the most investigated BCAA ( n = 9) [ 43 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 105 ], followed by valine ( n = 4) [ 43 , 97 , 98 , 104 ], and isoleucine ( n = 3) [ 43 , 98 , 99 ]. The studies performed by Brunner [ 43 ], Matsueda [ 97 ], and Mori [ 98 ] used all three BCAAs.…”
Section: Resultsmentioning
confidence: 99%
“…Leucine has also received consideration as a nutritional strategy to improve fetal growth as it has been shown to increase protein synthesis, resulting in increased skeletal muscle mass, as well as promote fetal pancreatic development and insulin secretion in fetal pigs and sheep (Wang et al 2018, Boehmer et al 2020. In the sheep study, leucine was infused into the fetal circulation in late gestation and potential impacts on placental function were not investigated (Boehmer et al 2020).…”
Section: Nutritional Strategies To Improve Placental Growth and Functionmentioning
confidence: 99%
“…Based on the concept that decreased fetal amino acid availability represents a key mechanism underpinning the development of IUGR, maternal amino acid supplementation has been contemplated [175,176] as a strategy to prevent and treat IUGR. It is possible that the positive effects of maternal supplementation with branched chain amino acids on fetal growth that has been reported in animals with normal sized and IUGR fetuses [45,177,178] may be due to activation of mTOR in the decidua, trophoblast, and the fetus. Given the recent successful development of in vivo trophoblast-specific gene targeting approaches in mice [179][180][181], it may be possible to design interventions that activate placental mTOR signaling in IUGR in the future.…”
Section: Placental Mtorc1 Activitymentioning
confidence: 99%
“…In contrast, whole-body deptor mutant KO mice are viable, fertile, and normal in size [37]. Moreover, there is a wealth of evidence that mTOR signaling plays an important role in the growth of individual fetal tissues and organs such as the intestine [38,39], beta cell [40,41], and skeletal muscle [42][43][44][45]. Similarly, decreased tissue growth is associated with inhibition of mTOR signaling in the fetal brown adipose [46], brain [47], heart [48], and thymus [49].…”
Section: Introductionmentioning
confidence: 99%